Secondary battery and electronic device

By setting tape between the first negative electrode sheet and the steel shell of the secondary battery and combining the use of fluorovinyl carbonate, the safety problem of the secondary battery under high temperature conditions is solved, and the reliability and high temperature safety of the battery are improved.

CN119890441APending Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510362412.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing secondary batteries have safety problems under high temperature conditions, especially the electrode components of steel-shell batteries are prone to short-circuit due to deformation of the steel shell, which affects the reliability of the battery.

Method used

By setting tape between the first negative electrode sheet and the steel shell, and controlling the ratio of the tape covering area to the first negative electrode sheet area is within the range of 0.2≤z/y≤0.95, combined with the use of a certain amount of fluorovinyl carbonate as the electrolyte component, the reliability of the use of the secondary battery and the high temperature safety are improved.

Benefits of technology

It effectively improves the safety of secondary batteries under high temperature conditions, reduces the risk of gas expansion and internal short circuit caused by side reaction between the electrolyte and the electrode at high temperature, and enhances the overall reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890441A_ABST
    Figure CN119890441A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage, and relates to a secondary battery and an electronic device. The secondary battery comprises an electrolyte, an electrode assembly and a steel shell, the electrode assembly comprises a positive pole piece, a negative pole piece and a diaphragm, the negative pole piece comprises a first negative pole piece and a second negative pole piece, the area of the first negative pole piece is y cm < 2 >, the first negative pole piece comprises a first current collector and a negative pole material layer arranged on one surface of the first current collector, and the surface, not provided with the negative pole material layer, of the first current collector is covered with gummed paper; the adhesive paper comprises a base material layer and adhesive layers arranged on the two surfaces of the base material layer, the adhesive layers comprise a first adhesive layer attached to the surface of the first negative pole piece and a second adhesive layer attached to the steel shell, the covering area of the adhesive paper is z cm < 2 >, and z / y is larger than or equal to 0.2 and smaller than or equal to 0.95; the electrolyte comprises fluoroethylene carbonate, the mass content of the fluoroethylene carbonate is a% by mass of the electrolyte, and a is greater than or equal to 1 and less than or equal to 40. Through cooperation of the gummed paper and the electrolyte, the use reliability of the secondary battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries, also known as rechargeable batteries or storage batteries, use the reversibility of chemical reactions to convert chemical energy into electrical energy during the discharge process. During the charging process, an external power source is used to restore the chemical system inside the battery so that it can discharge again. Secondary batteries are widely used in mobile devices, electric vehicles, energy storage systems and other fields due to their high energy density, long cycle life and low self-discharge rate. As the application scenarios of secondary batteries increase and their applications become more and more in-depth, higher requirements are also placed on their reliability. Summary of the invention

[0003] In view of this, the present application provides a secondary battery and an electronic device, which can effectively improve the reliability of the secondary battery through the combination of adhesive tape and electrolyte.

[0004] In a first aspect, the present application provides a secondary battery, including an electrolyte, an electrode assembly and a shell, wherein the shell is made of a steel shell; the electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, wherein a plurality of positive electrode sheets and a plurality of negative electrode sheets are alternately stacked, the separator is arranged between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet includes a first negative electrode sheet and a second negative electrode sheet, and the area of ​​the first negative electrode sheet is y cm 2 The first negative electrode plate includes a first current collector and a negative electrode material layer arranged on one surface of the first current collector along the thickness direction. The surface of the first current collector not provided with the negative electrode material layer is covered with adhesive paper. The adhesive paper includes a substrate layer and an adhesive layer. The adhesive layer includes a first adhesive layer and a second adhesive layer arranged on two surfaces of the substrate layer along the thickness direction of the substrate layer. The first adhesive layer is attached to the surface of the first negative electrode plate, and the second adhesive layer is attached to the steel shell. The adhesive paper covers an area of ​​zcm 2 , 0.2≤z / y≤0.95; the electrolyte includes fluoroethylene carbonate, and the mass content of fluoroethylene carbonate is a%, 1≤a≤40, based on the mass of the electrolyte. Adhesive tape is pasted between the first negative electrode plate and the steel shell, and the adhesive tape coverage area and the first negative electrode plate area are controlled to meet the above relationship. A certain amount of fluoroethylene carbonate is used in combination, which can effectively improve the reliability of the secondary battery, especially improve the safety under high temperature conditions.

[0005] In some preferred embodiments, 0.3≤z / y≤0.8. Controlling the ratio of the adhesive tape area to the area of ​​the first negative electrode plate within the above range can improve both the structural stability of the electrode assembly and the electronic conductivity, thereby further improving the high temperature safety of the secondary battery.

[0006] In some preferred embodiments, 2≤a≤20. Controlling the content of fluoroethylene carbonate within the above range can ensure the battery's electrical performance while reducing the side reactions between the electrolyte and the electrode at high temperatures, thereby further improving the high temperature safety of the secondary battery.

[0007] In some embodiments, 4≤y≤150. A suitable area of ​​the negative electrode plate can not only ensure that the battery has certain electrical properties, but also improve the heat dissipation of the battery, and further improve the high temperature safety of the secondary battery.

[0008] In some embodiments, the second negative electrode plate includes a second current collector and a negative electrode material layer disposed on two surfaces of the second current collector in the thickness direction, the thickness of the second current collector is 4 μm to 15 μm, the thickness of the first current collector is greater than the thickness of the second current collector, and the thickness difference is b μm, 3≤b≤20. The first current collector is relatively thick, which can ensure the electrical performance of the first negative electrode plate and maintain the stability of the overall structure of the battery.

[0009] In some embodiments, the substrate layer includes at least one of polyethylene terephthalate, polyimide, and polypropylene, and the adhesive layer includes at least one of acrylic resin, polyethylene glycol, and polymethyl methacrylate. The substrate of the above material has a certain mechanical strength and good insulation and temperature resistance, which can provide the necessary mechanical strength and support for the adhesive tape, so that it is not easy to deform or damage during use; the adhesive layer material has good viscosity and good anti-aging, heat resistance and thermal stability, which can make the adhesive tape firmly adhere to the negative electrode plate and the shell.

[0010] In some embodiments, the thickness of the adhesive tape is 11 μm to 50 μm, the thickness of the first adhesive layer is 3 μm to 10 μm, the thickness of the second adhesive layer is 3 μm to 10 μm, and the thickness of the substrate layer is 5 μm to 30 μm. The above configuration can make the adhesive tape have certain mechanical properties without being too thick to affect the energy density and structural stability of the battery.

[0011] In some embodiments, the electrolyte includes at least one of the following additives: succinic anhydride, citraconic anhydride, maleic anhydride, propanesulfonic anhydride, hexanetrinitrile, succinonitrile, 1,2,4-tris(methanesulfonyloxy)butane, tetramethyltetravinylcyclotetrasiloxane, methylvinyl sulfate, ethoxypentafluorocyclotriphosphazene, triphenylphosphite, dioxolane, 1-propylphosphoric anhydride, propenyl-1,3-sultone, 2,4-butanesultone, busulfan, 2-methylglutaronitrile, N,N'-carbonylbis(1,2,4-triazole), triethyl phosphate, and suberonitrile, and the mass content of the additive is A%, 0.3≤A≤10 based on the mass of the electrolyte. The above additives can further improve the high temperature safety of the secondary battery by improving the SEI / CEI film, reducing high temperature side reactions, blocking chain heat release, and improving the flame retardancy of the electrolyte.

[0012] In some preferred embodiments, 0.5≤A≤6.

[0013] In a second aspect, the present application provides an electrochemical device, which includes the secondary battery described in any of the aforementioned schemes.

[0014] The beneficial effects of the present application are as follows: The present application provides a secondary battery, including an electrode assembly and a shell, wherein the shell is made of a steel shell; the electrode assembly includes an electrolyte, a positive electrode sheet, a negative electrode sheet, and a diaphragm, a plurality of positive electrode sheets and a plurality of negative electrode sheets are alternately stacked, the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet includes a first negative electrode sheet and a second negative electrode sheet, the area of ​​the first negative electrode sheet is y cm 2 The first negative electrode plate includes a first current collector and a negative electrode material layer arranged on one surface of the first current collector along the thickness direction. The surface of the first current collector not provided with the negative electrode material layer is covered with adhesive paper. The adhesive paper includes a substrate layer and adhesive layers arranged on two surfaces of the substrate layer along the thickness direction of the substrate layer. The adhesive layers include a first adhesive layer and a second adhesive layer. The first adhesive layer is bonded to the surface of the first negative electrode plate, and the second adhesive layer is bonded to the steel shell. The adhesive paper covers an area of ​​z cm 2 , 0.2≤z / y≤0.95; the electrolyte includes fluoroethylene carbonate, and the mass content of fluoroethylene carbonate is a%, 1≤a≤40, based on the mass of the electrolyte. Double-sided adhesive tape is provided between the steel shell and the first negative electrode plate to increase the stability of the battery structure and effectively prevent the plate from being squeezed and deformed by the steel shell; a certain content of fluoroethylene carbonate can reduce the side reaction between the electrolyte and the electrode at high temperature while ensuring the electrical performance of the battery, and reduce the gas expansion of the battery. The use of adhesive tape and fluoroethylene carbonate can effectively improve the reliability of the secondary battery and further improve the high temperature safety of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1A schematic diagram of a secondary battery according to an embodiment of the present application at a first viewing angle; Figure 2 A schematic diagram of a secondary battery according to another embodiment of the present application at a first viewing angle; Figure 3 A schematic diagram of a secondary battery according to another embodiment of the present application at a second viewing angle; Figure 4 A schematic diagram of a secondary battery according to another embodiment of the present application at a second viewing angle; Figure 5 A schematic diagram of a secondary battery according to another embodiment of the present application at a second viewing angle; Figure 6 This is a schematic diagram of the adhesive tape structure of an implementation scheme of the present application.

[0016] Reference numerals: 1-electrode assembly; 11-negative electrode sheet; 111-first negative electrode sheet; 112-second negative electrode sheet; 12-diaphragm; 13-positive electrode sheet; 2- Shell; 3-adhesive tape; 31-base material layer; 32-adhesive layer; 321-first adhesive layer; 322-second adhesive layer. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0018] In this application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inside", "outside", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions and positional relationships shown in the drawings or the positions or positional relationships in which the products of this application are usually placed when used. These terms are mainly used to better describe this application and its embodiments, and are not used to limit the indicated devices, elements or components to have specific positions, or to be constructed and operated in specific positions.

[0019] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0020] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0021] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.

[0022] Steel shell battery refers to a type of battery whose outer shell is a steel shell. The rigid outer shell can withstand greater external pressure and better protect the electrode assembly 1. At the same time, the steel shell also has the advantages of strong sealing, high corrosion resistance and low cost, so it has a wide range of application prospects. However, the electrode assembly 1 of the steel shell battery is more rigid than that of the soft pack battery, the pole piece is tightly wrapped, and the space between the pole piece and the steel shell is very small. When the steel shell is deformed by internal pressure or external pressure, this deformation will be transmitted to the electrode assembly 1, causing the electrode assembly 1 to move and deform, and causing problems such as internal short circuit of the battery, affecting the safe use of the battery. The inventor found that by pasting double-sided tape 3 on a negative pole piece closest to the steel shell 2 in the electrode assembly 1, a "buffer zone" can be provided between the electrode assembly 1 and the steel shell 2, while fixing the relative position of the electrode assembly 1 and the steel shell 2, effectively reducing or avoiding the deformation of the electrode assembly 1 by the steel shell.

[0023] Based on the above analysis, in the first aspect, the present application provides a secondary battery, including an electrolyte, an electrode assembly 1 and a shell, wherein the shell is made of a steel shell; the electrode assembly 1 includes a positive electrode sheet 13, a negative electrode sheet 11, and a separator 12, a plurality of positive electrode sheets 13 and a plurality of negative electrode sheets 11 are alternately stacked, the separator 12 is arranged between the positive electrode sheet 13 and the negative electrode sheet 11, the negative electrode sheet 11 includes a first negative electrode sheet 111 and a second negative electrode sheet 112, and the area of ​​the first negative electrode sheet 111 is y cm 2 The first negative electrode plate 111 includes a first current collector and a negative electrode material layer arranged on one surface of the first current collector along the thickness direction. The surface of the first current collector not provided with the negative electrode material layer is covered with adhesive tape 3. The adhesive tape 3 includes a substrate layer 31 and an adhesive layer 32. The adhesive layer 32 includes a first adhesive layer 321 and a second adhesive layer 322 arranged on two surfaces of the substrate layer 31 along the thickness direction of the substrate layer 31. The first adhesive layer 321 is attached to the surface of the first negative electrode plate 111, and the second adhesive layer 322 is attached to the steel shell 2. The coverage area of ​​the adhesive tape 3 is z cm 2, 0.2≤z / y≤0.95; the electrolyte includes fluoroethylene carbonate, and the mass content of fluoroethylene carbonate is a%, based on the mass of the electrolyte, and 1≤a≤40. Exemplarily, the value of z / y can be 0.2, 0.35, 0.48, 0.56, 0.67, 0.72, 0.8, 0.85, 0.95 or a range consisting of any two of the above values; the value of a can be 1, 5, 8, 15, 20, 26, 32, 40 or a range consisting of any two of the above values. The "surface" here can be the entire area of ​​the negative electrode collector or a partial area of ​​the negative electrode collector. There is no special limitation in this application, as long as the purpose of this application can be achieved. There is no special limitation on the material of the negative electrode collector in this application, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite collector, etc.

[0024] See also Figure 1 , Figure 2 In the present application, the first negative electrode sheet 111 refers to a negative electrode sheet close to the steel shell 2, and the remaining negative electrode sheets are the second negative electrode sheets 112, and the adhesive tape 3 is arranged between the first negative electrode sheet 111 and the steel shell 2. It can be understood that the first negative electrode sheet 111 is coated on one side, that is, the side of the first negative electrode sheet 111 close to the steel shell 2 is not provided with an active material layer, and the side close to the positive electrode is provided with an active material layer. This design can facilitate the pasting of the adhesive tape 3, thereby achieving the effect described in the present application. Controlling the area ratio of the adhesive tape 3 to the first negative electrode sheet 111 within the above range can ensure the structural stability of the electrode assembly 1 while not affecting the electronic conduction. Further, in the present application, a certain amount of fluoroethylene carbonate is added to the electrolyte, and a certain amount of fluoroethylene carbonate can reduce the side reaction of the electrolyte and the electrode at high temperature while ensuring the electrical performance of the battery, and reduce the gas production and expansion of the battery. Under the joint action of fluoroethylene carbonate and adhesive tape 3, the use reliability of the secondary battery described in the present application can be effectively improved. It should be noted that the "covered area of ​​adhesive tape" refers to the area where the first adhesive layer 321 and the first negative electrode plate 111 are attached, or the area where the second adhesive layer 322 and the housing 2 are attached, and these two areas are the same. This application does not limit the specific shape and quantity of the adhesive tape 3, see Figure 1~Figure 5 The adhesive tape 3 can be one piece, two pieces, or multiple pieces, and can also be square, circular, or other shapes, as long as the area ratio of the adhesive tape 3 and the first negative electrode plate 111 in this application is satisfied.

[0025] In some preferred embodiments, 0.3≤z / y≤0.8. Controlling the area ratio of the adhesive tape 3 to the area ratio of the first negative electrode plate 111 within the above range can better conduct electrons while maintaining the stability of the battery assembly, thereby further improving the high temperature safety of the secondary battery. Exemplarily, the value of z / y can be 0.3, 0.36, 0.45, 0.52, 0.66, 0.77, 0.8, or a range consisting of any two of the above values.

[0026] In some preferred embodiments, 2≤a≤20. Controlling the content of fluoroethylene carbonate within the above range can better improve the battery electrical performance, reduce the side reaction between the electrolyte and the electrode at high temperature, and improve the high temperature stability of the secondary battery. For example, the value of a can be 2, 5, 8, 10, 12, 15, 20 or a range consisting of any two of the above values.

[0027] In some embodiments, 4≤y≤150. The area of ​​the appropriate negative electrode plate 11 can ensure that the battery has certain electrical properties without affecting the heat dissipation of the battery. Exemplarily, the value of y can be 4, 10, 20, 50, 80, 100, 120, 150, or a range consisting of any two of the above values.

[0028] In some embodiments, the second negative electrode plate 112 includes a second current collector and a negative electrode material layer disposed on two surfaces of the second current collector in the thickness direction, the thickness of the second current collector is 4 μm to 15 μm, the thickness of the first current collector is greater than the thickness of the second current collector, and the thickness difference is b μm, 3≤b≤20. A current collector of a certain thickness can not only ensure the electrical properties of the first negative electrode plate 111, but also maintain the stability of the overall structure of the battery. Compared with the double-sided coated second negative electrode plate 112, the single-sided coated first negative electrode plate 111 will cause asymmetric bending of the plate during rolling, winding or lamination due to the difference in thermal expansion coefficients between the coating layer and the current collector. A thicker current collector can provide higher bending stiffness and reduce the risk of warping, breaking or delamination of the plate. Exemplarily, the thickness of the second current collector can be 4 μm, 5 μm, 7 μm, 10 μm, 12 μm, 13 μm, 15 μm or a range consisting of any two of the above values; the value of b can be 3, 5, 8, 10, 12, 16, 17, 20 or a range consisting of any two of the above values.

[0029] In some embodiments, the substrate layer 31 includes at least one of polyethylene terephthalate, polyimide, and polypropylene, and the adhesive layer 32 includes at least one of acrylic resin, polyethylene glycol, and polymethyl methacrylate. The substrate of the above materials has certain mechanical strength, good insulation performance, and heat resistance, and can provide the necessary mechanical strength and support for the adhesive tape 3, so that it is not easy to deform or damage during use; the adhesive layer 32 material has good viscosity, and has good anti-aging, heat resistance, and thermal stability, so that the adhesive tape 3 can be firmly attached to the negative electrode plate and the shell.

[0030] In some embodiments, the thickness of the adhesive tape 3 is 11 μm to 50 μm; the thickness of the first adhesive layer 321 is 3 μm to 10 μm, the thickness of the second adhesive layer 322 is 3 μm to 10 μm, and the thickness of the substrate layer 31 is 5 μm to 30 μm. By controlling the thickness of the adhesive tape 3 and the substrate layer 31 within the above range, the adhesive tape 3 and the substrate layer 31 can have certain mechanical properties without being too thick to affect the energy density and structural stability of the battery. By controlling the thickness of the first adhesive layer 321 and the second adhesive layer 322, the adhesive tape can have a certain viscosity to fix the electrode assembly 1 and the steel shell 21 without affecting the overall thickness of the adhesive tape 3. The thickness of the first adhesive layer 321 and the second adhesive layer 322 can be the same or different, and this application does not limit this. Exemplarily, the thickness of the adhesive tape 3 can be 11 μm, 13 μm, 15 μm, 20 μm, 24 μm, 30 μm, 35 μm, 40 μm, 48 μm, 50 μm or a range consisting of any two of the above values; the thickness of the first adhesive layer 321 and the second adhesive layer 322 can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range consisting of any two of the above values ​​respectively; the thickness of the substrate layer 31 can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 28 μm, 30 μm or a range consisting of any two of the above values.

[0031] In some embodiments, the electrolyte includes at least one of the following additives: succinic anhydride, citraconic anhydride, maleic anhydride, propanesulfonic anhydride, hexanetrinitrile, succinonitrile, 1,2,4-tris(methanesulfonyloxy)butane, tetramethyltetravinylcyclotetrasiloxane, methylvinyl sulfate, ethoxypentafluorocyclotriphosphazene, triphenylphosphite, dioxolane, 1-propylphosphoric anhydride, propenyl-1,3-sultone, 2,4-butanesultone, busulfan, 2-methylglutaronitrile, N,N'-carbonylbis(1,2,4-triazole), triethyl phosphate, and suberonitrile, and the mass content of the additive is A%, 0.3≤A≤10 based on the mass of the electrolyte. The above additives can enhance the thermal safety of the battery by forming SEI / CEI films, reducing high-temperature side reactions, blocking chain heat release, and improving the flame retardancy of the electrolyte. Illustratively, the value of A can be 0.3, 1, 3, 5, 7, 8, 9, 10, or a range consisting of any two of the above values.

[0032] In some preferred embodiments, 0.5≤A≤6. The additive in the above content range can better enhance the thermal safety of the battery. For example, the value of A can be 0.5, 1, 2, 4, 5.2, 6 or a range consisting of any two of the above values.

[0033] The present application has no special restrictions on the positive electrode, as long as the purpose of the present application can be achieved. For example, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode active material layer located on at least one surface of the positive electrode current collector" means that the positive electrode active material layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved.

[0034] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0035] The positive electrode active material layer of the present application includes a positive electrode active material. The present application has no particular limitation on the type of the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide [LiNi 0.90 Co 0.05 Mn 0.05O2 (NCM955), NCM811, NCM622, NCM523, NCM111], lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate. In the present application, the positive active material may also contain non-metallic elements, such as non-metallic elements including at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive current collector and the positive active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5μm to 20μm, and the thickness of the single-sided positive active material layer is 30μm to 120μm.

[0036] In the present application, the positive electrode active material layer may further include a positive electrode binder and a positive electrode conductor. The present application does not particularly limit the type of positive electrode binder in the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0037] The present application has no particular restrictions on the type of positive electrode conductive agent in the positive electrode active material layer, as long as the purpose of the present application can be achieved. In some embodiments, the positive electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the loading amount of the positive electrode active material in the positive electrode sheet is 4.0 mg / cm 2 Up to 10.0 mg / cm 2 .

[0038] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular restrictions on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOx (0.5 <x <1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O12 , Li-Al alloy or metallic lithium, etc. The negative electrode material layer of the present application also includes a binder. The present application has no special restrictions on the binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder can be at least one of the above binders. The negative electrode material layer of the present application also includes a conductive agent. The present application has no special restrictions on the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent can be at least one of the above conductive agents. The present application has no special restrictions on the mass ratio of the negative electrode active material, the binder and the conductive agent in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0039] In the present application, the secondary battery also includes a diaphragm, which is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters [for example, polyethylene terephthalate (PET) film], cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0040] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0041] The secondary battery in the present application also includes a tab, which can lead the current out of the electrode assembly. The tab may include a positive tab and a negative tab, which are connected to the positive current collector substrate and the negative current collector substrate respectively. The tab may be formed by cutting or trimming the current collector substrate, or may be connected by welding. The present application does not limit the number, position, formation method, etc. of the tab.

[0042] The present application does not particularly limit the type of secondary battery, which may include any device that generates an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0043] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with adhesive tape to obtain an electrode assembly of the stacked structure, placing the electrode assembly in a housing, injecting the electrolyte into the housing and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the housing as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0044] In a second aspect, the present application provides an electronic device, comprising the secondary battery described in any of the aforementioned schemes.

[0045] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0046] The following is an example of a lithium-ion battery and the scheme of the present application is described in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from ordinary commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0047] Test methods and equipment: Hot box test: At 25°C, let the secondary battery stand for 5 minutes, charge to 4.5V at 0.5C constant current, then charge to 0.025C at 4.5V constant voltage, let stand for 60 minutes, and then conduct hot box test on the secondary battery. Before the hot box test, check the appearance of the secondary battery and take a photo, attach the temperature sensing line, place the secondary battery vertically in the hot box, heat it from 25°C to 130°C at a rate of 5°C / minute and keep it for 60 minutes. If the secondary battery does not catch fire or explode, it is considered to have passed the hot box test. The number of secondary battery samples tested is 100, and the number of batteries that passed the hot box test is counted and the pass rate of the hot box test is calculated.

[0048] Example 1-1 <Preparation of Electrolyte> In a dry argon atmosphere glove box, lithium hexafluorophosphate was dissolved in a solution containing fluoroethylene carbonate and diethyl carbonate. Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate was 12.5%, the mass content of fluoroethylene carbonate was 20%, and the balance was diethyl carbonate.

[0049] <Preparation of negative electrode sheet> Preparation of the first negative electrode sheet: artificial graphite, anode active material, Super P, thickener sodium carboxymethyl cellulose (CMC), and negative electrode binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1.5:0.5:1.6, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 30wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 20 µm, and dried at 110°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer. After coating, the negative electrode sheet was cold pressed and cut into a specification of 41 mm×61 mm for standby use.

[0050] Preparation of the second negative electrode sheet: artificial graphite, anode active material, Super P, thickener sodium carboxymethyl cellulose (CMC), and negative electrode binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 96.4:1.5:0.5:1.6, and then deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 30wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10µm, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side, and then the above steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After coating, the negative electrode sheet is cold pressed and cut into a specification of 41 mm×61 mm for standby use.

[0051] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode binder polyvinylidene fluoride (PVDF), and the positive electrode conductive agent Super P are mixed in a mass ratio of 97:1.6:1.4, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and stirred evenly. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 110°C to obtain a positive electrode sheet coated with a single-sided positive electrode active material. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a double-sided positive electrode active material. After the coating is completed, the positive electrode sheet is cold pressed and cut into a positive electrode sheet with a specification of 38 mm×58 mm for standby use.

[0052] <Diaphragm> A polyethylene-polypropylene film with a thickness of 7 μm was used.

[0053] <Preparation of Electrode Assembly> The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a barrier role. The positive and negative electrode sheets and the separator are stacked and formed at one time using a one-time molding technology, and the pole ears are welded to obtain an electrode assembly.

[0054] <Attaching tape and assembling batteries> Cut a piece with an area of ​​10 cm 2 (25mm×40 mm), with a thickness of 28 μm (the thickness of the substrate layer is 20 μm, and the thickness of the first and second adhesive layers are both 4 μm). Figure 3 The adhesive tape is pasted on the electrode assembly and the steel shell at the position of the adhesive tape as shown, placed in a vacuum oven at 85°C for 12 hours to remove moisture, injected with the above-prepared electrolyte, and a lithium-ion battery is obtained after vacuum packaging, standing, and formation processes.

[0055] Example 1-2 to Example 1-10, Comparative Example 1-1 to Comparative Example 1-6 The difference from Example 1-1 is that the parameters are adjusted according to Table 1. The performance test results of each embodiment and comparative example are shown in Table 1.

[0056] Table 1

[0057] As shown in Table 1, by placing adhesive tape between the first negative electrode plate and the steel shell, controlling the adhesive tape coverage area z and the first negative electrode plate area y to satisfy 0.2≤z / y≤0.95, and using 1% to 40% fluoroethylene carbonate by mass (based on the mass of the electrolyte), the reliability of lithium-ion batteries can be effectively improved, especially the safety under high temperature conditions. In particular, when 0.3≤z / y≤0.8, 2≤a≤20, the pass rate of the hot box test of lithium-ion batteries is significantly higher, that is, the reliability and high-temperature safety of lithium-ion batteries are better.

[0058] Referring to Examples 1-1 to 1-10 and Comparative Examples 1-1 to 1-4, it can be seen that the value of z / y has a great influence on the reliability of lithium-ion batteries. When the value of z / y is within the range described in this application, the pass rate of the hot box test of lithium-ion batteries is 60% to 78%, the battery reliability is high, and the safety under high temperature conditions is good. When the value of z / y is less than the scope of this application, the pass rate of the hot box test of lithium-ion batteries is significantly reduced. In Comparative Example 1-2, z / y is equal to 0.1, and the pass rate of the hot box test of lithium-ion batteries is 45%; in Comparative Example 1-1, without setting adhesive tape, the pass rate of the hot box test is reduced to 15%, and the reliability of lithium-ion batteries is significantly reduced; and when the value of z / y is greater than the scope of this application, the pass rate of the hot box test is also lower than the value of z / y in the scope of this application. In Comparative Example 1-4, when z / y is equal to 0.98, the pass rate of the hot box test is reduced to 59%; in Comparative Example 1-3, when z / y is equal to 1, the pass rate of the hot box test is reduced to 57%.

[0059] Comparing Example 1-1 with Comparative Examples 1-5 and 1-6, when z / y and y are the same, compared with not adding fluoroethylene carbonate, after adding 20% ​​fluoroethylene carbonate, the pass rate of the hot box test is increased from 34% to 78%, which shows that the addition of fluoroethylene carbonate can significantly improve the reliability of lithium-ion batteries. When the mass content of the added fluoroethylene carbonate is 50%, which exceeds the range described in this application, the pass rate of the hot box test drops to 21%, and the reliability of the lithium-ion battery is worse than that without adding fluoroethylene carbonate.

[0060] In summary, the present application controls the tape coverage area and the first negative electrode plate area to meet the relationship described in the present application, and uses a certain amount of fluoroethylene carbonate to effectively improve the reliability of lithium-ion batteries, especially the safety of lithium-ion batteries under high temperature conditions.

[0061] Furthermore, by comparing Examples 1-1 to 1-10, it can be seen that the area of ​​the negative electrode plate within the scope of the present application can not only ensure that the battery has certain electrical properties, but also improve the heat dissipation of the battery. The hot box test pass rate is relatively high, which can further improve the high temperature safety of the lithium-ion battery.

[0062] Example 2-1 to Example 2-7 The difference from Example 1-1 is that the thickness of the current collector is adjusted according to the parameters shown in Table 2. The performance test results of each embodiment are shown in Table 2.

[0063] Table 2

[0064] Referring to Table 2, in Examples 2-1 to 2-4, the thickness of the first current collector and the thickness of the second current collector meet the range described in the present application, the pass rate of the hot box test of the lithium-ion battery is 71%~82%, and the reliability of use is high; in Example 2-5, the thickness of the first current collector is 3μm, and the thickness of the second current collector is 2μm, the thickness of the first current collector and the thickness of the second current collector are both smaller than the range described in the present application, and the pass rate of the hot box test is 60%; in Example 2-6, the thickness of the first current collector and the thickness of the second current collector are both within the range described in the present application, but the second current collector is thicker than the first current collector, and the pass rate of the hot box test is 59%; in Example 2-7, the thickness of the first current collector and the thickness of the second current collector are both greater than the range described in the present application, and the difference in thickness between the first current collector and the second current collector is greater than the range described in the present application, and the pass rate of the hot box test is 61%. Compared with Examples 2-1 to 2-4, the hot box test pass rate of Examples 2-5 to 2-7 is lower. It can be seen that the present application effectively ensures the reliability of lithium-ion batteries, especially their safety under high temperature conditions, by setting the thickness of the second current collector to 4μm~15μm, the thickness of the first current collector is greater than the thickness of the second current collector, and the thickness difference is 3μm~20μm.

[0065] Example 3-1 to Example 3-4 The difference from Example 1-1 is that the adhesive tape is adjusted according to the parameters shown in Table 3. The performance test results of each embodiment and comparative example are shown in Table 3.

[0066] Table 3

[0067] It can be seen from Table 3 that, compared with Example 3-1 and Example 3-2, the adhesive tape in Example 3 is thicker overall, the substrate layer and the adhesive layer are thicker, and the pass rate of the hot box test is lower than that of the adhesive tape with a thickness within the scope of this application; in Example 4, the adhesive tape is thinner overall, the substrate layer and the adhesive layer are thinner, and the pass rate of the hot box test is also lower than that of the adhesive tape with a thickness within the scope of this application. It can be seen that controlling the thickness of the adhesive tape, the first adhesive layer, the second adhesive layer and the substrate layer can effectively improve the pass rate of the hot box test of lithium-ion batteries, improve the reliability of battery use, and especially the safety of lithium-ion batteries under high temperature conditions.

[0068] Example 4-1 to Example 4-9 The difference from Example 1-1 is that the content and type of the additives are adjusted according to the parameters shown in Table 4. The performance test results of each embodiment are shown in Table 4.

[0069] Table 4

[0070] Comparing Example 1-1 with Example 4-1 to Example 4-9, it can be seen that when the electrolyte further includes the above-mentioned additives, and the type and mass content of the additives are within the range described in this application (the above-mentioned additive ratio is a mass ratio), the battery hot box test pass rate is improved. This shows that when the above-mentioned additives are added to the electrolyte and the mass content of the additives is controlled within a certain range, the reliability of lithium-ion batteries can be effectively improved, especially the safety of lithium-ion batteries under high temperature conditions.

[0071] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery, characterized in that: The secondary battery comprises an electrolyte, an electrode assembly and a housing, wherein: The shell is made of steel; The electrode assembly comprises a positive electrode sheet, a negative electrode sheet, and a separator, wherein a plurality of the positive electrode sheets and a plurality of the negative electrode sheets are alternately stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet; The negative electrode sheet includes a first negative electrode sheet and a second negative electrode sheet, and the area of ​​the first negative electrode sheet is y cm 2 The first negative electrode plate comprises a first current collector and a negative electrode material layer arranged on one surface of the first current collector along the thickness direction, the surface of the first current collector not provided with the negative electrode material layer is covered with adhesive paper, the adhesive paper comprises a substrate layer and an adhesive layer, the adhesive layer comprises a first adhesive layer and a second adhesive layer arranged on two surfaces of the substrate layer along the thickness direction of the substrate layer, the first adhesive layer is bonded to the surface of the first negative electrode plate, the second adhesive layer is bonded to the steel shell, and the adhesive paper coverage area is z cm 2 , 0.2≤z / y≤0.95; The electrolyte includes fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate is a%, based on the mass of the electrolyte, and 1≤a≤40.

2. The secondary battery according to claim 1, characterized in that: 0.3≤z / y≤0.

8.

3. The secondary battery according to claim 1, characterized in that: 2≤a≤20。 4. The secondary battery according to claim 1, characterized in that: 4≤y≤150。 5. The secondary battery according to claim 1, characterized in that: The second negative electrode plate includes a second current collector and a negative electrode material layer arranged on two surfaces of the second current collector along the thickness direction, the thickness of the second current collector is 4 μm~15 μm, the thickness of the first current collector is greater than the thickness of the second current collector, and the thickness difference is b μm, 3≤b≤20.

6. The secondary battery according to claim 1, characterized in that: The substrate layer includes at least one of polyethylene terephthalate, polyimide, and polypropylene, and the adhesive layer includes at least one of acrylic resin, polyethylene glycol, and polymethyl methacrylate.

7. The secondary battery according to claim 1, characterized in that: The thickness of the adhesive tape is 11 μm to 50 μm, the thickness of the first adhesive layer is 3 μm to 10 μm, the thickness of the second adhesive layer is 3 μm to 10 μm, and the thickness of the substrate layer is 5 μm to 30 μm.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: The electrolyte includes at least one of the following additives: succinic anhydride, citraconic anhydride, maleic anhydride, propanesulfonic anhydride, hexanetrinitrile, succinonitrile, 1,2,4-tris(methanesulfonyloxy)butane, tetramethyltetravinylcyclotetrasiloxane, methyl vinyl sulfate, ethoxypentafluorocyclotriphosphazene, triphenylphosphite, dioxolane, 1-propyl phosphoric anhydride, propenyl-1,3-sultone, 2,4-butanesultone, busulfan, 2-methylglutaronitrile, N,N'-carbonylbis(1,2,4-triazole), triethyl phosphate, and suberonitrile. Based on the mass of the electrolyte, the mass content of the additive is A%, and 0.3≤A≤10.

9. The secondary battery according to claim 8, characterized in that: 0.5≤A≤6。 10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-voltage lithium ion battery and electrolyte thereof

    CN104269577A

  • Electrochemical device and electronic device comprising the same

    CN115398706A

  • Battery cell, battery with battery cell and manufacturing method of battery cell

    CN116914269A

  • Lithium polymer battery

    KR1020010068555A